MENINGKATKAN KEAKTIFAN BELAJAR SISWA MELALUI PENGGUNAAN MEDIA APLIKASI WORDWALL PADA MATA PELAJARAN BAHASA INDONESIA DIKELAS 2 DI SD NEGERI 28/IV KOTA JAMBI - Hady Wijaya; Nazurty; Eddy Haryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Wordwall is an application that can be used as an interesting learning medium for students, a learning resource, or an online assessment tool. Wordwall Media provides solutions to improve student learning outcomes through various interactive game concepts. To achieve Indonesian language skills, this must be followed by media that can make it easier for students to learn or understand. One way to develop vocabulary in Indonesian is to use Word Wall media. The aim of this research is: To find out how to increase student learning activity through the use of Wordwall Application Media in Indonesian Language Subjects in Class 2 at SD Negeri 28/IV Jambi City for the 2023/2024 Academic Year. The type of research used is Classroom Action Research. Classroom Action Research is research carried out in the classroom, to solve problems that exist in the classroom. Based on the research data, it can be concluded that the learning media Wordwall Application Media can increase student learning activity in Indonesian language subjects in class 2 at SD Negeri 28/IV Jambi City. The research results obtained from teacher observation activities reached 64.5%, and the 2nd meeting was 88%, the results of student observations reached 59% with the 2nd meeting 72%. Therefore, the percentage results show that using the Wordwall application can increase students' learning activity. They look more enthusiastic, not bored and very happy when learning and evaluating at the end of each lesson using the wordwall application. The conclusion from these achievements is that learning using the Wordwall Application Media can increase student learning activity in the learning process.